Pemberian Grasi oleh Pemerintah Indonesia kepada Narapidana Kasus Narkoba Schapelle Corby - Nadia, Citra; Hanura, Marten (Journal of International Relations, 2018)
This study describes the pardon granted by the Government of Indonesia to Corby underthe Government of Susilo Bambang Yudhoyono in the case of drug crimes committed bySchapelle Leigh Corby, and explains the reasons of Indonesia under the administration ofPresident Susilo Bambang Yudhoyono in granting clemency to Corby. The method used inprocessing the data is by qualitative method, by analyzing the data of the identifiedmaterial sources, such as interviews, international agreements, and other sources such asscholarly documents, articles, journals, or scientific writing on similar themes with thisresearch. The concept in this study explains that bilateral cooperation in achieving thenational interest of each country is very influential on foreign policy applied by state actors.It also affects Indonesia and Australia in cooperating. International cooperation is a toolfor international relations actors whose function is to facilitate and serve a variety ofunlimited activities. Foreign Policy has a national importance for a country and is anobjective of the national Government at the international level. Governments within acountry, of course, have a goal to promote and prosper the country by making policies andconnecting with other countries. The Indonesian government grants clemency toAustralian citizen inmates involved in narcotics case Schapelle Leigh Corby on an interestbasis. Corby was found guilty of having found 4.2 kilograms of brutto or 4.1 kilograms netin his surfboard satchel at Ngurah Rai airport, Bali on October 8, 2004. Corby's grant wasmade on the basis of the Government of Indonesia's wishes and interests to Australia.